Expression of CD73 and A2A receptors in cells from subjects with obesity and type 2 diabetes mellitus - Guzman-Flores, Juan M.; Cortez-Espinosa, Nancy; Cortés-Garcia, Juan D.; Vargas-Morales, Juan M.; Cataño-Cañizalez, Yolanda G.; Rodríguez-Rivera, Jaime G.; Portales-Perez, Diana P. (Immunobiology (1979), 2015)
Regulatory T cells have various mechanisms to suppress the inflammatory response, among these, the modulation of the microenvironment through adenosine and with the participation of CD39, CD73 and A2A. The aim of this study was to assess the expression of CD73 and A2A in immune cells and the effect of activation of A2A by an adenosine analogue on apoptosis in patients with obesity and type 2 diabetes mellitus (T2D). CD73 and A2A expression were analyzed by flow cytometry in lymphocyte subpopulations from patients with obesity (n=22), T2D (n=22), and healthy subjects (n=20). Lymphocytes were treated with the selective A2A antagonist (ZM241385) or the selective A2A agonist (CGS21680), and apoptotic cells were detected by Annexin V. We found an increased expression of CD39 coupled to a decrease in CD73 in the patient groups with obesity and T2D compared to the control group in the different studied lymphocyte subpopulations. A2A expression was found to be increased in different subpopulations of lymphocytes from T2D patients. We also detected positive correlations between CD39+ cells and age and BMI. Meanwhile, CD73+ cells showed negative correlations with age, WHR, BMI, FPG, HbAc1, triglycerides and cholesterol. Moreover, an increase in the percentage of apoptotic cells from T2D patients with regard to the groups with obesity and control was observed. In addition, the CD8+ T cells of patients with T2D exhibited decreased apoptosis when treated with the A2A agonist. In conclusion, our data suggest a possible role for CD73 and A2A in inflammation observed in patients with T2D and obesity mediated via apoptosis.